Sloths host Anhanga virus‐related phleboviruses across large distances in time and space. Issue 1 (5th September 2019) - de Oliveira Filho, Edmilson F.; Moreira‐Soto, Andrés; Fischer, Carlo; Rasche, Andrea; Sander, Anna‐Lena; Avey‐Arroyo, Judy; Arroyo‐Murillo, Francisco; Corrales‐Aguilar, Eugenia; Drexler, Jan Felix
Abstract: Sloths are genetically and physiologically divergent mammals. Phleboviruses are major arthropod‐borne viruses (arboviruses) causing disease in humans and other animals globally. Sloths host arboviruses, but virus detections are scarce. A phlebovirus termed Anhanga virus (ANHV) was isolated from a Brazilian Linnaeus's two‐toed sloth ( Choloepus didactylus ) in 1962. Here, we investigated the presence of phleboviruses in sera sampled in 2014 from 74 Hoffmann's two‐toed ( Choloepus hoffmanni, n  = 65) and three‐toed ( Bradypus variegatus, n  = 9) sloths in Costa Rica by broadly reactive RT‐PCR. A clinically healthy adult Hoffmann's two‐toed sloth was infected with a phlebovirus. Viral load in this animal was high at 8.5 × 10 7  RNA copies/ml. The full coding sequence of the virus was determined by deep sequencing. Phylogenetic analyses and sequence distance comparisons revealed that the new sloth virus, likely representing a new phlebovirus species, provisionally named Penshurt virus (PEHV), was most closely related to ANHV, with amino acid identities of 93.1%, 84.6%, 94.7% and 89.0% in the translated L, M, N and NSs genes, respectively. Significantly more non‐synonymous mutations relative to ANHV occurred in the M gene encoding the viral glycoproteins and in the NSs gene encoding a putative interferon antagonist compared to L and N genes. This was compatible with viral adaptation to different sloth species and with micro‐evolutionary processes associated with immune evasion during the genealogy of sloth‐associated phleboviruses. However, gene‐wide mean dN/dS ratios were low at 0.02–0.15 and no sites showed significant evidence for positive selection, pointing to comparable selection pressures within sloth‐associated viruses and genetically related phleboviruses infecting hosts other than sloths. The detection of a new phlebovirus closely‐related to ANHV, in sloths from Costa Rica fifty years after and more than 3, 000 km away from the isolation of ANHV confirmed the host associations of ANHV‐related phleboviruses with the two extant species of two‐toed sloths.